(untitled) (Bangladesh Journal of Pharmacology, 2012)
To investigate the relationship between the suppression of Hydroxysafflor yellow A (HSYA) on the oxidized low density lipoprotein (ox-LDL) induced proliferation of vascular smooth muscle cells (VSMCs) and the mRNA and protein expression of extracellular signal-regulated protein kinase 1/2 (ERK1/2) and mitogen activated protein kinase phospholipase-1 (MAKP-1), VSMCs were treated with HSYA at 10 ?mol/L and/or ox-LDL at 35 mg/L for 48 h. MTT assay was done to measure cell survival rate, flow cytometry to detect cell cycle, reverse transcription PCR and Western blot to detect the expression of ERK1/2 and MAKP-1. When compared to cells treated with ox-LDL alone, the survival rate of cells treated with two reagents was reduced and the proportion of cells in G0/G1 phase significantly increased, with increased MKP-1 expression. The study suggests HSYA can inhibit VSMC proliferation via increasing MKP-1 expression, reducing p-ERK1/2 activity and suppressing cell cycle.